Evidence-Informed Deliberative Processes for UHC: Progress, Potential and Prudence; Comment on "Evidence-Informed Deliberative Processes for Health Benefit Package Design - Part II: A Practical Guide" - Unni Gopinathan (Kerman University of Medical Sciences, 2023)
In their recent article on evidence-informed deliberative processes (EDPs) for health benefit package decisions, Oortwijn et al examine how the different steps of EDP play out in eight countries with relatively mature institutions for using health technology assessment (HTA). This commentary examines how EDP addresses stakeholder involvement in decision-making for equitable progress towards universal health coverage (UHC). It focuses on the value of inclusiveness, the need to pay attention to trade-offs between desirable features of EDP and the need to broaden the scope of processes examined beyond those specifically tied to producing and using HTAs . It concludes that EDPs have contributed to significant progress for health benefit design decisions worldwide and holds much potential in further application. At the same time, this commentary calls for prudence: investments in EDPs should be efficiently deployed to enhance the pre-existing legislative, institutional and political framework that exist to promote fair and legitimate healthcare decisions.